(untitled) (The Peerian Journal, 2024)
The article discusses the main research methods used in the methodology of teaching the Russian language. Theoretical, empirical and experimental approaches, their features, advantages and areas of application are analyzed. Special attention is paid to innovative methods, including the use of digital technologies, corpus analysis and data visualization Russian language